Collaborative Governance in Hydrometeorological Disaster Mitigation in Sukabumi City - Salma Normalina; Dian Purwanti; M Rijal Amirulloh (Prediksi : Jurnal Administrasi dan Kebijakan, 2026)
The high frequency of hydrometeorological disasters in Sukabumi City makes collaborative governance among actors a fundamental necessity in disaster mitigation. Although mitigation efforts have been supported by formal regulations and institutional frameworks, the effectiveness of their implementation is strongly influenced by the quality of collaborative governance established among stakeholders. This study aims to analyze collaborative governance in hydrometeorological disaster mitigation in Sukabumi City using the Ansell and Gash (2007) model, encompassing starting conditions, institutional design, facilitative leadership, and collaborative process. A descriptive qualitative approach was employed through in-depth interviews, observation, and document study, involving BPBD, Bappeda, Dinas Sosial, Dinas PUPR, KNPI, and PWI Sukabumi City as informants. The findings indicate that collaborative governance has been established through multi-stakeholder engagement, the formation of the Disaster Risk Reduction Forum (FPRB), and the Disaster-Resilient Village program. However, collaboration remains constrained by the unrenewed legal basis of the FPRB, the absence of standardized cross-institutional operational guidelines, dependence on particular leadership figures, and suboptimal information sharing among stakeholders. This study concludes that collaborative governance in Sukabumi City has been formed but has not yet reached an optimal level, thus requiring strengthened institutional frameworks, regulations, and coordination mechanisms to ensure consistent and sustainable collaboration.